PENGARUH KEBIJAKAN DIVIDEN DAN KEBIJAKAN HUTANG TERHADAP HARGA SAHAM (Studi Kasus : LQ45 di Bursa Efek Indonesia (BEI) - Efendi, Muklis; Susilawati, R. Anastasia Endang; Sari, Ati Retna (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2015)
This study aims to examine and explain the interrelationships between the variables dividend policy and debt policy on stock prices . In addition, this study also wants to determine the effect of a variable dividend policy and debt policy on stock prices. Data used in this research is quantitative data, while sumberdata used in this study are secondary data from the company's annual report. This study used purposive sampling method and obtained 15 LQ45 company listed in Indonesia Stock Exchange with a four-year study period is 2009-2012. The analysis used is multiple regression analysis at a significance level of 0.05 % . The results of this study indicate that in partial dividend policies have a significant effect on stock prices . For debt policy variable has no significant effect on stock prices . While simultaneously dividend policy and debt policies have a significant effect on stock prices.